Assessment of Mutakallimūn's Negative Common Views on Nature of Moral Goodness and Badness - Taleqani SayyedAli; Hossein Rafiei (اخلاق وحیانی, 2023)
What is moral goodness and moral badness? This is one of the most important questions in metaethics. Mu'tazila and Imami theologians have given different answers to this question, but their most frequent analysis of goodness and badness can be placed in three main groups: negative analysis, positive analysis, and analysis containing elements of reward or divine punishment. We call these three groups of analysis "common analysis" for short. In this paper, the first group of common analysis, i.e. negative analysis, are formulated and then evaluated. First, we have formulated the differences of opinion and ambiguities in this group of analysis of moral goodness and badness in the form of different readings of the negative analysis, and then we have examined and evaluated each one. Among the problems of different readings, we can mention the following: 1) Negative analysis do not have a sufficient conditions to be good. 2) These analysis imply the false or controversial assumption that no conscious and voluntary action is devoid of moral value. 3) In many of these analysis, good act and bad act are confused with good actor or bad actor. 4) These analysis define good and bad based on condemnation and non-condemnation, while praising and condemning an act is not necessarily moral and may be, for example, based on criteria aimed at immoral, expedient or aesthetic goals. In the last section, there are additional problems with negative analysis that lack the element of entitlement.